2016
DOI: 10.14356/kona.2016025
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monodispersed Nanoparticles of Transparent Conductive Oxides

Abstract: Generally, indium-tin-oxides (ITO) thin film is prepared by the sputtering process with ITO target, but only 20 % of ITO yielded from the target is deposited on the substrate. Namely, about 80 % ITO is exhausted by the deposition elsewhere far from the substrate. The recycling process of indium is limited so that ca. 20 % ITO of the starting material is lost without any recovery. Even if the recycling of ITO has been carried out in this process, we should prepare ITO target of 5 times more than apparent use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…S2 † ). 20 Nevertheless, in order to ensure the integration of only one or two ITO NPs per inverse micelle, the NPs had to be fully dispersed in the water phase, i.e. no aggregates of ITO NPs were allowed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2 † ). 20 Nevertheless, in order to ensure the integration of only one or two ITO NPs per inverse micelle, the NPs had to be fully dispersed in the water phase, i.e. no aggregates of ITO NPs were allowed.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, as previously reported, solvothermal and sol-gel methods were used to synthesize the ITO NPs. 20 The starting compounds Ta 6 Br 14 (H 2 O) 4 $3H 2 O (TBH) and K 4 Nb 6 Br 18 (KNB) were synthesized according to a procedure that was previously published. 30,31 The experimental conditions for the microemulsion process were adapted from our previous work.…”
Section: Preparation Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution process based on printing technology offers an opportunity to reduce the fabrication costs from the following viewpoints: (1) efficient materials utilization due to direct deposition of the desired material at a location where it should be patterned and (2) low investment cost of the manufacturing equipment and easy scalability for large-area electronics since the printing technology does not require complicated and expensive vacuum-based equipment [11][12][13][14][15]. Despite these advantages of the solution process, it is reported by many research groups that the material performance of the solution-prepared ITO films needs to be further improved compared to the sputtered ITO films [16][17][18]. The sheet resistance of the solution-prepared ITO films is usually one-order higher than that of the sputtered films with a similar transparency.…”
Section: Introductionmentioning
confidence: 99%